Lipophilic prodrugs of nucleoside triphosphates as biochemical probes and potential antivirals - Gollnest, Tristan (Nat Commun, 2015)
The antiviral activity of nucleoside reverse transcriptase inhibitors is often limited by ineffective phosphorylation. We report on a nucleoside triphosphate (NTP) prodrug approach in which the γ-phosphate of NTPs is bioreversibly modified. A series of TriPPPro-compounds bearing two lipophilic masking units at the γ-phosphate and d4T as a nucleoside analogue are synthesized. Successful delivery of d4TTP is demonstrated in human CD4(+) T-lymphocyte cell extracts by an enzyme-triggered mechanism with high selectivity. In antiviral assays, the compounds are potent inhibitors of HIV-1 and HIV-2 in CD4(+) T-cell (CEM) cultures. Highly lipophilic acyl residues lead to higher membrane permeability that results in intracellular delivery of phosphorylated metabolites in thymidine kinase-deficient CEM/TK(−) cells with higher antiviral activity than the parent nucleoside.